1995
DOI: 10.1002/ajmg.1320590318
|View full text |Cite
|
Sign up to set email alerts
|

Inversion duplication of the short arm of chromosome 8: Clinical data on seven patients and review of the literature

Abstract: We report on clinical and cytogenetic data on 5 children and 2 adults with a de novo inverted duplication of the short arm of chromosome 8, and we give a review of 26 patients from the literature. The clinical picture in young children is characterized by minor facial anomalies, hypotonia, and severe developmental delay. In older patients the facial traits are less characteristic, spastic paraplegia develops, and severe orthopedic problems are frequent. Psychomotor retardation is always severe-to-profound. Dup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 10 publications
3
53
0
1
Order By: Relevance
“…Multiple patients with duplication and trisomy of 8p have been reported. [3][4][5][6][7] Many of the previously reported clinical finding were similar.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Multiple patients with duplication and trisomy of 8p have been reported. [3][4][5][6][7] Many of the previously reported clinical finding were similar.…”
Section: Discussionsupporting
confidence: 66%
“…In some of those patients, prominent forehead, high arched palate, large mouth with a thin upper lip, malformed and/or apparently lowset ears, broad nasal bridge, dental and skeletal abnormalities, and joint laxity were noted. de DieSmulders et al [4] reported on five children and two adults with duplication of 8p. They found that minor facial anomalies, hypotonia, and severe developmental delay were noticeable in the children, while in older patients the facial traits were less characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some of them, originally interpreted as direct duplications on pure cytogenetic analysis, turned out to be complex rearrangements after proper molecular analysis showing not only a duplicated but also a deleted region. The studies on the inv dup(8p), a recurrent rearrangement associated with a rather characteristic syndrome, 9 revealed that it derives by nonallelic homologous recombination between lowcopy repeats. 7,8,10 Other examples of inv dup are those concerning 1q, 11,12 24 suggesting that the mechanism responsible for the inv dup(8p) can be generalized to all inverted duplications.…”
Section: Discussionmentioning
confidence: 99%
“…14 The clinical picture of patients with duplication of much of 8p was described as a recognizable multiple congenital anomalies such as facial anomalies, hypotonia, structural brain abnormalities, and mental retardation syndrome while profound orthopedic problems, spastic paraplegia, frequently develop in elder patients. [22][23][24] In the database of DECIPHER v8.7, there were 2 cases having a chromosomal aberration mostly analogous to us. One case (Patient 249443) had a 3.41 Mb duplication at 8p22 to 8p21.3 (chr8:18403254-21816649, encompassing 11 genes [ATP6V1B2 (ATPase, H+ transporting, lysosomal, V1 subunit B2), CSGALNACT1, DOK2 (Docking protein 2), GFRA2 (GDNF family receptor alpha 2), INTS10 (Integrator complex subunit 10), LPL (Lipoprotein lipase), LZTS1 (Leucine zipper, putative tumor suppressor 1), PSD3, SH2D4A, SLC18A1 (Solute carrier family 18 member 1), and XPO7 (Exportin 7)], inheritance unknown), with the phenotypes such as autism, inguinal hernia, intellectual disability, long face, macrocephaly, macrotia, proportionate short stature, and seizures; the other (Patient 249579) also had a 3.41 Mb duplication at 8p22 to 8p21.3 (chr8:18403338-21816628, encompassing genes the same as above, inheritance unknown), with a clinical picture of autism, brachycephaly, cryptorchidism, intellectual disability, proptosis, short philtrum, short toe, spasticity, and upslanted palpebral fissure.…”
Section: Discussionmentioning
confidence: 84%